Optimization Biodiesel Production from Honge Oil (Pongamia Pinnata) - Nandkishore, D.; Sanjay, Patil; Abhijit, Dandavate; Krishna, Gaikwad Mahesh (Communications - Scientific Letters of the University of Zilina, 2024)
Rapid industrialization and increased diesel engine usage have driven up diesel consumption, burdening economies with heavy petroleum product imports. Diesel fuel emissions, including carbon dioxide, carbon monoxide, and smoke, pose environmental concerns. Biodiesel produced from non-edible vegetable oils offers a sustainable solution.
Keywords: diesel consumption; biodiesel; Honge oil; Taguchi method; optimization; sustainable alternative